2018
DOI: 10.1097/prs.0000000000003926
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tranexamic Acid in Plastic Surgery: Review and Technical Considerations

Abstract: Minimizing blood loss during surgery is critical, and many modalities have been used to decrease unwanted surgical bleeding. Among many methods, use of pharmacologic agents such as antifibrinolytic drugs has been shown to significantly reduce blood loss and the rates of postoperative blood transfusion in many articles. Tranexamic acid is an antifibrinolytic agent that has been widely used in other surgical specialties, especially in cardiac, orthopedic, and trauma surgery. Despite its known benefits, the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 65 publications
1
70
0
2
Order By: Relevance
“…Tranexamic acid (TXA), a lysine derivative with a structure similar to that of lysine, can be combined with lysine targets on the plasminogen and plasminogen to block the interaction between fibrin and heavy chain of plasmin, thus promoting the coagulation process and achieving the goal of controlling postoperative blood loss. [ 10 , 11 ] Substantial studies have reported that TXA could reduce blood products and cost after joint arthroplasty surgery. [ 12 14 ] However, there still exists controversy regarding the efficacy of TXA administration in long-segment spinal fusion surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Tranexamic acid (TXA), a lysine derivative with a structure similar to that of lysine, can be combined with lysine targets on the plasminogen and plasminogen to block the interaction between fibrin and heavy chain of plasmin, thus promoting the coagulation process and achieving the goal of controlling postoperative blood loss. [ 10 , 11 ] Substantial studies have reported that TXA could reduce blood products and cost after joint arthroplasty surgery. [ 12 14 ] However, there still exists controversy regarding the efficacy of TXA administration in long-segment spinal fusion surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Topical TXA is gaining popularity as a simple, low-cost intervention to reduce surgical bleeding 23 . The present study has shown that that limited topical exposure to TXA is well tolerated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Topical application is receiving increasing attention, as it is inexpensive and simple, and may reduce bleeding from all surgical surfaces. 25 Large studies from joint replacement surgery have confirmed that topical use of tranexamic acid reduces blood loss at least as well as intravenous administration. 2630 Studies from cardiac and thoracic surgery are fewer, smaller, and not unambiguous.…”
mentioning
confidence: 99%